Aplikasi Operasi Matriks pada Perancangan Simulasi Metode Hill Cipher Menggunakan Microsoft Excel - Endaryono Endaryono; Nurfidah Dwitiyanti; Heri Satria Setiawan (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
One of several algorithms in cryptography is the Hill Cpher method. This method is used in randomizing the contents of the message using a password key in the form of a matrix with the order MXM. The product in this research is a simulation design to explain how a plaintext message is converted into cipher text with encryption and decryption processes and vice versa from ciphertext to paintext through multiplication and inverse matrix operations. using Microsoft Excel (MS Excel). In this study, a matrix with order 2x2 and modulo 26 was used. This simulation design shows how the work process visually for each step in the process of changing the message content in the Hill Cipher method. It is hoped that the results of this study can be used as a learning medium by the community, especially students and lecturers, to increase understanding and broaden their horizons about the Hill Cipher method in cryptography lectures.